MR VOLUMETRY AND HISTOGRAM ANALYSIS IN THE DIAGNOSIS OF LOCALLY ADVANCED RECTAL CANCER - Janković, Aleksandra; Kovač, Jelena (Medicinski podmladak, 2024)
Rectal cancer, a subtype of colorectal cancer, represents a major global health concern. Prompt and precise diagnosis is essential for selecting the best treatment techniques and enhancing the result itself. Imaging tools, particularly magnetic resonance imaging (MRI), have significantly contributed to the diagnosis and stage of the illness in recent years. MRI offers a comprehensive visualization of rectal cancer and its adjacent structures due to its superior ability to capture fine details of soft tissues and generate images from several angles. When evaluating the response to neoadjuvant chemoradiotherapy (nCRT) in patients with rectal cancer, it is crucial to acknowledge the significance of additional MRI parameters beyond those specified in the standard protocol. Volumetry and histogram analysis are sophisticated magnetic resonance imaging methods that show promise as additional tools for assessing tumor features and predicting therapeutic response. This paper aims to assess the significance of volumetric MRI and histogram analysis in diagnosing rectal cancer. It aims to clarify the specific benefits and limitations of each technique, thereby enhancing our understanding of their role and importance in the diagnosis of this disease.
Keywords: MRI, volumetry, histogram analysis, LARC, rectal carcinoma